PENGARUH PRICE DAN PRODUCT QUALITY TERHADAP PURCHASING DECISIONS IMPLORA CHEEK AND LIPTINT - Karisma Nurul Hidayah; Beta Asteria (JURNAL EKOBIS DEWANTARA, 2023)
This study aims to how the price and quality for Implora Cheek and Liptint products affect consumers' purchasing decisions in Yogyakarta City. The participants of this study were consumers who used Implora Cheek and Liptint in Yogyakarta City. Purposive sampling applied in this study, by a total sample of 100 respondentsts. Data retrieval techniques using questionnaires. To process data, SPSS ver. 25 is used. The study prove; price had a positive and significant effect on the purchasing decision of Implora Cheek and Liptint, product quality had a positive and significant effect on the purchasing decision of Implora Cheek and Liptint, price and product quality simultaneously have a positive and significant effect on purchasing decisions of Implora Cheek and Liptint.